2007
DOI: 10.1002/asi.20686
|View full text |Cite
|
Sign up to set email alerts
|

Information seeking behavior of academic scientists

Abstract: The information seeking behavior of academic scientists is being transformed by the availability of electronic resources for searching, retrieving, and reading scholarly materials. A census survey was conducted of academic science researchers at the University of North Carolina at Chapel Hill to capture their current information seeking behavior. Nine hundred two subjects (26%) completed responses to a 15-minute Web-based survey. The survey questions were designed to quantify the transition to electronic commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
113
2
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 143 publications
(131 citation statements)
references
References 25 publications
7
113
2
6
Order By: Relevance
“…These findings are similar to findings by Hemminger et al (2007) who found that researchers prefer electronic journals and scientific databases for searching and accessing scholarly information. …”
Section: Information Use Behaviour Of Researcherssupporting
confidence: 90%
See 1 more Smart Citation
“…These findings are similar to findings by Hemminger et al (2007) who found that researchers prefer electronic journals and scientific databases for searching and accessing scholarly information. …”
Section: Information Use Behaviour Of Researcherssupporting
confidence: 90%
“…Researchers from different disciplines have different information needs and take different approaches to satisfy these information needs (Gannon-Leary, Bent & Webb, 2008;Hemminger, Vaughan & Adams, 2007;Herman, 2001;Schonfeld & Guthrie, 2007;Sheeja, 2010;Tennant & Cataldo, 2002). Some authors argue that librarians need to have more knowledge about the subject fields in which their users are involved (Allan, 2010;Brophy, 2008;Schonfeld & Guthrie, 2007).…”
Section: Information Needs and Information Behaviour Of Veterinariansmentioning
confidence: 99%
“…A complete copy of the original questionnaire and a more detailed description is available in Hemminger et al (2007). A copy of the final revised multi-institution survey (not including introductory and closing pages) is available at http://ils.unc.edu/bmh/ isb/National-ISB-Survey.pdf and is included in Appendix question, which was tailored by site to uniquely identify the participants' department.…”
Section: Survey Questionnairementioning
confidence: 99%
“…However, in the era of electronic/printed journals, online access has been gradually recognized to be important. [14][15][16][17] Scientific publishers have taken full advantage of this feature. Once a paper is accepted, it becomes rapidly available online on some journals' websites.…”
Section: Discussionmentioning
confidence: 99%